"There's always something else": Patient perspectives on improving the implementation of obesity guidelines in general practice. Issue 5 (September 2020) - Mazza, D.; McCarthy, E.; Singh, N.; Carey, M.; Turner, L.; Harris, M.
Abstract: Objectives: The prevalence of obesity in Australia is rising. National guidelines for the management of overweight and obesity exist but our previous work demonstrates poor implementation of key elements in general practice. The aim of this study was to describe patient perspectives on the implementation of obesity guidelines in general practice. Methods: Qualitative study of 40 people living with obesity (PwO) who were recruited through general practices in Melbourne, Australia. PwO had a recorded BMI in the overweight range or above (>25), had attended a consultation in the last 6 months and had a diagnosis of at least one of the following: diabetes, kidney disease, hyperlipidemia, hypertension, or cardiovascular disease. Semi-structured telephone interviews were conducted with patients. Interviews were audio-recorded, transcribed verbatim and analysed thematically. Results: While a strong general practitioner (GP)-patient relationship enabled conversation to occur about weight management there was uncertainty as to whether patients or GPs should broach the topic of weight. Patients described complacency regarding their weight and often being unprepared to take up GP advice. Other health issues were felt to take precedence, and patients described inconsistent provision of information and resources to assist them in tackling their weight problems. Conclusions: It is imperative to take into account patient perspectives on obesity management in general practice in order to improve health outcomes. This study provides valuable insights into how PwO can be better managed. Interventions should also include strategies to help patients maintain motivation in making lifestyle changes to support healthy weight loss.